2021
DOI: 10.1590/1980-5373-mr-2020-0508
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application in Crude Oil-Water Separation of Clay-Based Membranes

Abstract: In this study, tubular ceramic membranes were prepared from a mixture of ball clay, talc and alumina. The mixture was characterized by the following techniques: particle size analysis, X-ray fluorescence spectroscopy (XRF), X-ray diffraction (XRD) and thermal analysis. Tubular membranes were produced by extrusion process and thermal treated at temperatures between 1025 °C and 1175 °C. The membranes were characterized by XRD, linear shrinkage, apparent porosity, flexural strength, mercury porosimetry, scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…These values remain relatively lower than those reported by some researchers for low-cost-developed ceramic membranes. It is worth mentioning that for the low-cost ceramic membranes prepared by Vasanth et al 2013 [53], Souza et al 2021 [54], Emani et al 2013 [18] and Suresh et al 2016 [55] the estimated cost was found as 55-58, 97, 130 and 15-40 ($/m 2 ), respectively.…”
Section: Membranes' Cost Estimationmentioning
confidence: 99%
“…These values remain relatively lower than those reported by some researchers for low-cost-developed ceramic membranes. It is worth mentioning that for the low-cost ceramic membranes prepared by Vasanth et al 2013 [53], Souza et al 2021 [54], Emani et al 2013 [18] and Suresh et al 2016 [55] the estimated cost was found as 55-58, 97, 130 and 15-40 ($/m 2 ), respectively.…”
Section: Membranes' Cost Estimationmentioning
confidence: 99%
“…In general, the flexural strength of ceramic membrane tends to enhance with increasing sintering temperature and decreasing porosity (Sahnoun & Baklouti 2013;Guechi et al 2016;Wang et al 2016;Hubadillah et al 2016cHubadillah et al , 2019dHubadillah et al , 2020Abdulhameed et al 2017aAbdulhameed et al , 2017bMohamed Bazin et al 2019;Li et al 2020b;Ndjigui et al 2021;Souza et al 2021). Based on the above-observed results, it can be said that a metakaolin-based flat sheet membrane sintered at 1,300, 1,400, and 1,500 °C has a sufficient flexural strength compared to a membrane sintered at 1,200 °C.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Many traditional techniques are used to treat oily water, such as solvent extraction [2], catalytic cracking [3], mechanical centrifugation [4][5][6], membrane separation [7][8][9], gravity [10,11], biodegradation [12][13][14][15], mechanical recovery by oil skimmers [16], and many others. However, many reports can be found in the literature about the low separation efficiency, secondary pollution generation, high costs to synthesize and transport materials, large equipment needed, and many other drawbacks that restrict the use of these methods [15].…”
Section: Introductionmentioning
confidence: 99%